Effects of grape seedlings intercropping with post-Grafting generation of Cosmos sulphureus on different fractions of cadmium content in soil. Issue 4 (February 2019) - Zhong, Lisha; Liu, Na; Xia, Dan; Lin, Lijin; Liao, Ming'an
Abstract: A pot experiment was conducted to study the effects of grape seedlings intercropping with post-grafting generation of Cosmos sulphureus on different fractions of cadmium (Cd) in soil. The results showed that when grape seedlings intercropped with the generation of ungrafted C. sulphureus (I CK), the content of exchangeable Cd increased by 25%, and the content of residual Cd decreased by 17% compared to the monoculture, respectively. Compared to the monoculture, grape seedlings intercropping with the post-grafting generation of self-rooted grafting by two uniform plant seedlings of C. sulphureus (I UG) significantly increased the residual Cd content (37%) while the exchangeable Cd content increased not significantly (11%). In conclusion, the treatment of I CK was not conducive to the reduction of the bioavailability of Cd in soil, while the treatment of I UG was better.